Peculiarities of serum levels of vascular growth factor and its receptors in dialysis patients - Driianska, V.; Dudar, I.; Shifris, I.; Poroshina, T.; Savchenko, V.; Kononova, G. (Ukrainian Journal of Nephrology and Dialysis, 2022)
Recent research has shown that VEGF may influence the condition and survival of patients with chronic kidney disease (CKD), including those treated with dialysis procedures. Identifying the value of this factor is important to uncover the mechanisms of CKD progression and improve treatment strategies. The present study aimed to determine the mean serum levels of vascular endothelial growth factor (VEGF) and its receptor (VEGF-R) and their correlations with pro-inflammatory cytokines (TNF-α, MCP-1, IL -6, IL -8) in dialysis patients stratified by dialysis modality and Carnivit use. Methods. In this prospective cohort study, serum levels of VEGF, VEGF-R, and proinflammatory cytokines were determined in 41 hemodialysis (HD) patients (group 1) and 14 peritoneal dialysis (PD) patients (group 2), 28 of whom were treated with Carnivit. The assay was performed with the enzyme immunoassay "SunRise TouchScreen" using IBL International (Germany) test systems. The limits of normal values (reference range) were determined based on the results of a study with 20 conditionally healthy individuals. Results. All included patients had significantly higher serum levels of VEGF compared to healthy donors (p=0.006); a significant increase in this mediator was observed in both HD and PD treated subjects (p=0.002 and p=0.007, respectively). Carnivit treatment resulted in a significant decrease (p=0.023) in this mediator to normal levels in all patients. Subgroup analysis showed a significant decrease in VEGF (p=0.016) and VEGF-R (p=0.005) in HD patients after therapy. Mean concentrations of growth factor in HD patients (p=0.098) and PD patients (p=0.160) did not differ from those of healthy subjects. A positive correlation was observed between serum levels of VEGF and its receptors in the studied patients both before and after treatment (p < 0.0001). A direct correlation between IL -8 and VEGF and VEGF-R was observed in HD patients and an inverse correlation between MCP-1 and VEGF-R was observed in PD patients. After Carnivit treatment, the correlation between serum levels of IL -8 and VEGF-R (0.782, p=0.01) and between VEGF and VEGF-R (0.770, p=0.01) remained in group 1 and between VEGF and VEGF-R (0.829, p=0.03) in group 2. Conclusion. Increased concentrations of VEGF and its receptors were detected in the blood of dialysis patients, with a positive correlation between them and the pro-inflammatory IL -8. Treatment with Carnivit resulted in a significant decrease in cytokines with the maintenance of the balance between vascular growth factor and its receptors, which we consider a positive effect for the inhibition of inflammation with the progression of endothelial dysfunction.